Smartphone connectivity stress across generations: Validation of a brief scale for adolescents and adults - Cherie A. Clark (Elsevier, 2021)
Research into problematic smartphone use is growing as people are increasingly dependent on technological connections – a situation highlighted during the COVID-19 pandemic. However, current research has been limited by measurement validity issues and a lack of construct clarity. In response, this study developed and validated the Smartphone Connectivity Stress Scale (SCSS) for adolescents and adults. An online survey included an item pool, based on previous research and existing scales, as well as several psychosocial measures (N ​= ​814; aged 14–80 years; 59% female). Iterative exploratory factor analyses, classical test theory and item response theory (IRT) analyses produced a unidimensional six-item scale of smartphone connectivity stress – from a perceived obligation to be constantly connected with others. Two-week test-retest reliability was assessed through a follow up survey (n ​= ​190). SCSS factor structure and reliability were strong for adolescents (aged 14–18) and adults (aged 19–80). The SCSS demonstrated good internal consistency (α ​= ​0.87, ωt ​= ​0.91); test-retest reliability, r ​= ​0.82; and all items captured significant information across the latent trait. The SCSS demonstrated no differential item functioning by sex, age, ethnicity or urban/rural residence. The SCSS was positively correlated (ps ​< ​.001) with anxious attachment style and psychopathology symptoms (stress, anxiety, depression, suicidality). This is the first measure of smartphone connectivity stress and included valuable IRT analyses. The brief public domain SCSS provides reliable measurement, with reduced error, of a validated construct, and is suitable for use with adolescents and adults.